Edukasi Kesehatan Diabetes Melitus dan Senam Kaki: Diabetes Mellitus Health Education and Foot Exercises - Hutapea, Adventina Delima; Cathryne, Joice; Sihombing, Riama Marlyn; Sitorus, Fiolenty Bertina Marulianna; Sitanggang, Yenni Ferawati (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
Diabetes mellitus is the main cause of health complications that can be fatal and cause complications in several systems. Diabetes mellitus significantly increases healthcare costs and harms the quality of life of human resources. Therefore, all stakeholders, including the government and the community, must participate in efforts to prevent this disease. A therapy that can help prevent complications of diabetes mellitus includes education and regular diabetic foot exercises. This community service activity aimed to increase public awareness about diabetes mellitus and its prevention through foot exercises. This activity included education, diabetic foot exercises, and health screening. The participants in this activity were community members of HKBP Lippo Karawaci, which began with a pre-test, a presentation of the material, discussion, foot exercises, a post-test, and health screening. The total number of participants was 65. Based on the analysis, the average pre-test score was 60.18, and the post-test score was 61.11. The analysis showed that participants’ knowledge had increased, although the difference was minimal, in line with the indicator of an increase of >10%. This activity concludes that health education can improve participants’ understanding of diabetes mellitus and enable them to participate in diabetic foot exercise programs. To enhance awareness and prevent diabetes mellitus complications from an early stage, it is recommended that similar activities be conducted on an ongoing basis and integrated into health promotion initiatives.